2002
DOI: 10.1103/physrevlett.89.266804
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous Low-Field Classical Magnetoresistance in Two Dimensions

Abstract: The magnetoresistance of classical two-dimensional electrons scattered by randomly distributed impurities is investigated by numerical simulation. At low magnetic fields, we find for the first time a negative magnetoresistance proportional to |B|. This unexpected behavior is shown to be due to a memory effect specific for backscattering events, which was not considered previously.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
98
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(103 citation statements)
references
References 17 publications
5
98
0
Order By: Relevance
“…Nevertheless, the dependance of these corrections on the magnetic field turns out to be very sharp, resulting in the MR anomaly. The anomaly was discovered in recent numerical simulations [15] where the MR in a system of 2D electrons scattering on randomly distributed hard disks was studied. This system is usually referred to as the Lorenz gas and is the simplest model of the 2D electron gas with strong scatterers.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…Nevertheless, the dependance of these corrections on the magnetic field turns out to be very sharp, resulting in the MR anomaly. The anomaly was discovered in recent numerical simulations [15] where the MR in a system of 2D electrons scattering on randomly distributed hard disks was studied. This system is usually referred to as the Lorenz gas and is the simplest model of the 2D electron gas with strong scatterers.…”
mentioning
confidence: 89%
“…The anomaly was observed in the case β ≪ 1, β 0 ≪ 1. Both the numerical simulations and the qualitative analysis of [15] indicated that at zero temperature, T, the MR can be expressed in terms of a dimensionless function f (z) via…”
mentioning
confidence: 99%
“…However, for B = 0 the role of ME is dramatically increased due to a strong dependence of return probability on B. Recent studies demonstrated that ME lead to a variety of nontrivial magnetotransport phenomena in 2D disordered systems such as magnetic-field-induced classical localization [7,8], high-field negative [7,8,9,10, 11] and positive MR [12], low-field anomalous MR [13,14,15], and non-Lorentzian shape of cyclotron resonance [16].In spite of large number of publications, devoted to the study of the influence of the nonMarkovian effects on the MR, the dependence of R on B, induced by such effects, was investigated (to the best of our knowledge) only in the context of so-called "circling electrons" [7]. These electrons occupy closed cyclotron orbits which avoid scatterers.…”
mentioning
confidence: 99%
“…1c ′ ) thus decreasing (increasing) S 0 and leading to a sharp dependence of W on B. The corresponding correction to ρ xx was calculated numerically in [13] and analytically in [14].…”
mentioning
confidence: 99%
“…The observed LNMR, that is an anomalous behavior, reached up to 20 % of the zero field resistivity (ρ xx (B = 0)), however, in a very small region around B = 0, the resistivity showed a non-anomalous behavior. Recent theoretical developments for the conductivity of a classical two-dimensional Lorentz gas [8,9] allowed us to attribute this MR to non-Markovian memory effects originated by specific return processes in backscattering of electrons by corrugations and defects. However, a certain difference related to the order of magnitude of the full variation of ∆ρ xx /ρ xx (0) = [ρ xx (B) − ρ xx (0)]/ρ xx (0) appeared between the theoretical model and our experimental results.…”
Section: Introductionmentioning
confidence: 99%